Organization of health services in the family health strategy: perspectives of basic unit managers - Daniela Savi Geremia; Augusto Krindges; Jiennifer Souza de Oliveira; Jéssica Ferreira; Ianka Cristina Celuppi; Jeane Barros de Souza (Acta Scientiarum. Health Sciences, 2023)
To analyze the organization of services offered in the Family Health Strategy, from the perspective of Basic Units managers. Analytical, qualitative study, carried out through a focus group, with the participation of 25 managers of Basic Family Health Units in a pole city in the West of Santa Catarina. For systematization and data analysis, the Discourse of the Collective Subject was used, based on the theory of social representations, which resulted in three Central Ideas. Three Central Ideas emerged: ‘The influence of Structural Factors for the Development of Services in the Family Health Strategy’, ‘Care and management organization of work in the Family Health Strategy’ and ‘Access and user’s satisfaction from the perspective of Basic Health Units managers’. Some challenges were evidenced in management practices, such as inadequate infrastructure, professional turnover and conduct based on the medical-hegemonic model. The difficulty in offering comprehensive, individualized, and longitudinal care was emphasized, which directly influences user’s satisfaction. The health care model and the articulation of the network determine the forms of care and management organization of services, which impact on guaranteeing access and resolution in the care provided to users.